Genome sequencing and multi-stage, blood-feeding, and tissue-specific transcriptome atlas of the Rocky Mountain wood tick provide a critical resource for this vector - Joshua E. Tompkin; Perot Saelao; Justyna Kruczalak; Huiqing Yeo; Pia U. Olafson; Sheina B. Sim; Kennan Oyen; Melissa Kelley; Renee L. Corpuz; Brian Scheffler; Scott M. Geib; Anna K. Childers; et al. (Insect Biochemistry and Molecular Biology, 2026)

Comparing residential peak demand response under dynamic pricing and direct load control: impacts of program design and smart thermostat ownership - Mina Safari; Burak Gunay; Mohamed M. Ouf; Benoit Delcroix; Seyedsaeid Hosseini (Energy and Buildings, 2026)

Genomic insights into the evolutionary history and cryptic diversity of two-toed sloths (Choloepus) in Amazonia - Larissa S. Arantes; Luísa S. Marins; Linda Hagberg; Radarane Santos Sena; Benoit de Thoisy; Marta Svartman; Mariluce Rezende Messias; Cláudia R. Silva; Nicole M. Foley; William J. Murphy; Camila C. Ribas; Fabrício R. Santos; et al. (Molecular Phylogenetics and Evolution, 2026)

Disproportionate PFAS mass loading from landfill leachate: implications for biosolids management policy - Patrick M. D'Aoust; Benoit Barbeau; Sébastien Sauvé; Dwight Houweling (Journal of Environmental Management, 2026)

Reduced gene flow and high population structure in four species of Chresta (Compositae, Vernonieae) from the Brazilian Caatinga represent challenges for their conservation - Carolina M. Siniscalchi; Benoit Loeuille; José Rubens Pirani; Jennifer R. Mandel (Flora, 2026)

Palaeoecology of a conodont age-calibrated and spectacularly preserved bryozoan-brachiopod biostromal palaeocommunity from the Asselian of Carlin Canyon, Nevada, USA - Charles M. Henderson; Lucia Angiolini; Benoit Beauchamp (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effect of whole-body cryostimulation on skin temperature and thermal comfort in severe obese patients - Romain Bouzigon; Jacopo M. Fontana; Marjorie Delecray; Paolo Pitera; Federica Verme; Angelo Alito; Benoit Dugué; Paolo Capodaglio (Cryobiology, 2026)

Acoustic evidence for topographic blocking on a steep submarine canyon wall - Astrid B. Leitner; Chad M. Waluk; Kim R. Reisenbichler; Rob E. Sherlock; Bruce H. Robison; Kelly J. Benoit‐Bird (Limnology and Oceanography, 2026)
Diel vertical migration (DVM) is the largest mass‐movement of animals on Earth, with profound ecological and biogeochemical consequences. DVM has mostly been studied in the open ocean; however, at steep slopes, pelagic animals including vertical migrators must contend with the seafloor, emphasizing the importance of understanding DVM in these prevalent, critical habitats. Here we used active acoustics in combination with video to conduct a detailed study of the interactions of vertical migrators with the steep wall of a submarine canyon during their sunrise descent. We found regular and frequent, high‐density sunrise aggregations of animals consistent with seafloor blocking of descending vertical migrators across all seasons. While topographic blocking was thought to be primarily caused by nighttime advection of migrators over shallows by prevailing currents, here the occurrence of this phenomenon was observed to be largely independent of oceanographic drivers including advection as measured by an ADCP, providing evidence that behavior plays an important role. Advection, season, upwelling, and other environmental factors were found to impact specific characteristics of sunrise aggregations but not likelihood of occurrence. Given its intensity and prevalence, topographic blocking likely creates high‐quality, predictable foraging opportunities for a large diversity of predators and influences the abundance and habitat use of predators in the area. The steep slopes of this canyon, as with any abrupt bathymetry, juxtapose the deep and the shallow, the benthic and the pelagic, and the offshore and nearshore. Thus, topographic blocking may be prevalent in other steep canyons and at steep bathymetry more generally.

Resource variability shapes the ecology of social information and collective sensing - William K. Oestreich; Jenna E. Kohles; Briana Abrahms; Kelly J. Benoit-Bird; Andrew M. Berdahl; John P. Ryan; Dina K.N. Dechmann (Trends in Ecology & Evolution, 2026)

Phylogenetic Diversity and Dispersion of Ants Worldwide: Geographic Variation and Climatic Correlates - Hong Qian; Runxi Wang; Michael Kessler; Shenhua Qian; Jamie M. Kass; Evan P. Economo; Benoit Guénard (Global Ecology and Biogeography, 2026)
Aim Species composition in biological assemblages is driven by an interplay of evolutionary, environmental, and ecological processes. Investigating the relationships between evolutionary history and climatic conditions can shed light on the variation in biodiversity and phylogenetic structure in biological assemblages. Harnessing a global dataset of ant biodiversity, here we determine the extent to which climate drives geographic patterns of phylogenetic diversity and dispersion in ants. Methods We calculated mean pairwise distance (MPD, measuring phylogenetic diversity) and the standardized effect size of MPD (MPD ses , measuring phylogenetic dispersion) in each of over 11,500 ant assemblages, and related them to variables representing current climatic conditions and Quaternary climate change. Location Global. Time Period Current. Taxon Ants. Results We find that these two metrics are positively correlated with climate averages yet negatively correlated with climate variability. We also find that current climatic conditions are more strongly associated with these phylogenetic metrics than Quaternary climate change. Temperature variables had stronger associations than precipitation variables, and climate extremes and seasonality affected phylogenetic diversity and dispersion equally. Lastly, areas with higher phylogenetic diversity and dispersion tend to have more paleo‐endemic lineages. Main Conclusions The geographic patterns and climatic associations with ant phylogenetic diversity and dispersion found in this study are largely consistent with those found in butterflies and several plant groups, suggesting that the same mechanisms may have driven phylogenetic structure more broadly across the tree of life.

Muigaia, a new Paleotropical genus of Convolvulaceae - Simon Wachira Ngima; Vivian Kathambi; Samuel Paul Kagame; Sushant More; Lauren A. Eserman; Rafael Felipe de Almeida; Benoit Loeuille; Marc S. M. Sosef; Patrick Chalo Mutiso; Higor Antonio-Domingues; Lars W. Chatrou; Ana Rita Simões (Kew Bulletin, 2026)
Summary A new genus of Convolvulaceae, Muigaia , is here proposed and fully revised, including molecular phylogenetic analyses, comprehensive morphological and palynological descriptions, identification keys, distribution maps and conservation assessments. It is a strictly paleotropical genus, occurring in Tropical Africa, Madagascar, India and Australia, and remarkably absent from the Malesian region. It is distinctive for the markedly angular stems; deeply palmately lobed, irregularly dissected leaves; leaf-like stipules at the base of the petiole; muricate, verrucose or cristate sepals; a 3-globose stigma and a 6-valved capsule. A revision of the species involved in this complex has resulted in the recognition of a total of seven species, including five new combinations, one new name ( M. shimpalei ) and one newly described species ( M. australiana ), endemic to Australia. The tropical African specimens of M. coptica , in particular, exhibit a wide range of morphological variation and should be investigated in detail. We expect that, now that Muigaia has been phylogenetically and morphologically circumscribed, further revisionary studies could focus on improving the species delimitation, and likely result in the discovery of additional new species to science.

Dehydrating microhabitats increase mite activity and intensify ectoparasitism of Drosophila - Joshua B. Benoit; Gabrielle LeFevre; Joy Bose; Ann Miller; David Lewis; Hailie Talbott; Chandrima Das; Emily Susanto; Lyn Wang; Oluwaseun M. Ajayi; Shyh-Chi Chen; Michal Polak (Journal of Comparative Physiology B, 2026)
Parasites interact with their host in variable environments that are often subject to water scarcity and dehydration. Drosophilid fruit flies and associated ectoparasitic mites interact across a range of microhabitats, typically in decaying organic matter, such as fallen fruit and cactus tissue, that dries out and deteriorates over periods ranging from days to months. Here, we report that mite parasitism of Drosophila increases with exposure to increasingly dry conditions for two fly-mite systems ( D. nigrospiracula-Macrocheles and D. melanogaster-Gamasodes ). In D. melanogaster , artificial selection for increasing behavioral resistance did not eliminate this effect, as previously selected lines remained relatively more resistant than non-selected controls even under dry conditions. Water balance assays confirmed that mites became dehydrated when held under dry conditions, which was also associated with increased mite activity. Exposure of D. melanogaster to mites dehydrated by exposure to low relative humidity increased parasitism, further supporting that prevalence of infestation intensifies under dry conditions. The results indicate that ectoparasitism in this system is affected by the water content of the mites. The increased motivation of mites to parasitize flies under dry conditions may serve to replenish mite water stores and facilitate dispersal to more favorable microhabitats.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Atlantic-wide connectivity of Ascension Island green turtles revealed by finer-scale mitochondrial DNA markers - Sophia A. Coveney; Eva Jiménez-Guri; Samantha Ball; Nathalie Mianseko; Annette C. Broderick; Brendan J. Godley; Joana M. Hancock; Welton Quirino Pereira; Aissa Regalla; Rita Gomes Rocha; Cheibani Senhoury; Benoit de Thoisy; et al. (Conservation Genetics, 2025)
Marine turtles undertake long migrations across different geographies and habitats, exposing them to a wide range of threats throughout their lifespan. Analysing population structure and connectivity is key to informing effective conservation management. We expand knowledge of Atlantic-wide connectivity of green turtles ( Chelonia mydas ) by characterising the genetic structure of the Ascension Island nesting population, one of the largest in the Atlantic Ocean, and carrying out Atlantic population structure and mixed stock analyses using high-resolution genetic markers. We amplified a ~ 738 bp fragment (extended D-loop) and a highly polymorphic mitochondrial short tandem repeat (mtSTR) fragment of the mitochondrial DNA control region, designating haplotypes based on (1) extended D-loop and (2) the extended D-loop and mtSTR combined. Overall, 11 extended D-loop and 33 combined haplotypes were found, the dominant haplotypes being CM-A8.1 and CM-A8.1/7-12-4-4. Population structure analysis found three main genetic groups: Northwest Atlantic, Northern South America, and South and East Atlantic. Mixed stock analyses indicate Ascension Island as a major source for juvenile foraging aggregations in the Southwest Atlantic (34–55%) and Central Africa (18–78%), with some contribution to West Africa (3–20%). Green turtles are vulnerable to fishery bycatch in the coastal waters of the South and East Atlantic. Our study underlines how improving sample sizes of Atlantic mtSTR haplotypes could further elucidate green turtle connectivity across threatened regions. We urge international collaboration to minimise mtSTR data gaps, in order to enhance connectivity assessments and improve conservation measures between countries that share populations.

Tracking Aeromonas caviae and Pseudomonas aeruginosa in a mixed-use catchment with source attribution, health hazards, and microbial mixing assessments - Adrien C. M. Pozzi; Angélique Dominguez-Lage; Baptiste Luton; Laurence Marjolet; Delphine Mouniée; Emmanuelle Bergeron; Matthieu Masson; Cécile Miège; Marina Coquery; Pauline Dusseux; Nicolas Robinet; Véronica Rodriguez-Nava; et al. (Environmental Science and Pollution Research, 2025)

Role of phthalates in breast cancer initiation, progression and drug rersistance: A scoping review and recommendations - L. Benoit; C. Tomkiewicz; S. Bortoli; A.S. Bats; X. Coumoul; M. Koual (Toxicology Letters, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

P31-24 Pharmacological validation of integrated nerve conduction velocity assays, functional observational battery and videotracking in the rat using peripheral nerve toxicants - A. Chefdeville; C. Bory; M. Terasse; V. Benoit; M. Latzko; N. Sadekova; A. Brown; S. Baudet (Toxicology Letters, 2025)

Seasonality and local nutrient loading drive changes in organic carbon in seagrass ecosystems in Hong Kong - Amrit Kumar Mishra; Katie M. Watson; Ho Tun Ng; Man Zhao; Chanaka Isuranga Premarathne Maha Ranvilage; Dwi Wai Shan Jaimie; Tse Cham Man; Christelle Not; Benoit Thibodeau; Juan C. Astudillo; Juan Diego Gaitán-Espitia (Estuarine, Coastal and Shelf Science, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Visualizing the structural and chemical heterogeneity of fruit and vegetables using advanced imaging techniques: fundamentals, instrumental aspects, applications and future perspectives - Weijie Lan; Xiao Hui; Bart Nicolaï; Pieter Verboven; Jianwei Qin; Catherine M. G. C. Renard; Benoit Jaillais; Kang Tu; Sylvie Bureau; Leiqing Pan (Critical Reviews in Food Science and Nutrition, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Viviparity and obligate blood feeding: tsetse flies as a unique research system to study climate change - Joshua B Benoit; Hester Weaving; Callum McLellan; John S Terblanche; Geoffrey M Attardo; Sinead English (Current Opinion in Insect Science, 2025)

Tau from SPAM Transgenic Mice Exhibit Potent Strain-Specific Prion-Like Seeding Properties Characteristic of Human Neurodegenerative Diseases - Ethan D. Smith; Giavanna Paterno; Brach M. Bell; Kimberly-Marie M. Gorion; Stefan Prokop; Benoit I. Giasson (NeuroMolecular Medicine, 2025)

A half-century of nuclear research, education and training: Story of the JSI TRIGA reactor - Luka Snoj; Klemen Ambrožič; Loïc Barbot; Ljudmila Benedik; Arne Bratkič; Ivana Capan; Christelle Reynard-Carette; Vladimir Cindro; Dušan Čalič; Christophe Destouches; Benoit Geslot; Alireza Haghighat; et al. (Annals of Nuclear Energy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Evolution of the occurrence of phytomelanin in aerial stems of American Vernonieae subtribes (Asteraceae) - Josiane Wolff-Coutinho; Benoit Francis Patrice Loeuille; Carolina M. Siniscalchi; Fábio Vitalino Santos Alves; Fernanda Maria Cordeiro de Oliveira; Ana Claudia Rodrigues; Makeli Garibotti Lusa (Flora, 2025)

How coevolution in daily activity rhythms governs encounters between predator and prey - Etienne Sirot; Thomas Benoit; Frédéric M. Hamelin (Animal Behaviour, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Scaling up ocean conservation through recognition of key biodiversity areas in the Southern Ocean from multispecies tracking data - Sarah L. Becker; Charlotte Boyd; Jonathan M. Handley; Ben Raymond; Ryan Reisinger; Yan Ropert‐Coudert; Nora Apelgren; Tammy E. Davies; Mary‐Anne Lea; Mercedes Santos; Philip N. Trathan; Anton P. Van de Putte; et al. (Conservation Biology, 2025)
Biodiversity is critical for maintaining ecosystem function but is threatened by increasing anthropogenic pressures. In the Southern Ocean, a highly biologically productive region containing many endemic species, proactive management is urgently needed to mitigate increasing pressures from fishing, climate change, and tourism. Site‐based conservation is one important tool for managing the negative impacts of human activities on ecosystems. The Key Biodiversity Area (KBA) Standard is a standardized framework used to define sites vital for the persistence of global biodiversity based on criteria and quantitative thresholds. We used tracking data from 14 species of Antarctic and subantarctic seabirds and pinnipeds from the publicly available Retrospective Analysis of Antarctic Tracking Data (RAATD) data set to define KBAs for a diverse suite of marine predators. We used track2kba, an R package that supports identification of KBAs from telemetry data through identification of highly used habitat areas and estimates of local abundance within sites. We compared abundance estimates at each site with thresholds for KBA criteria A1, B1, and D1 (related to globally threatened species, individual geographically restricted species, and demographic aggregations, respectively). We identified 30 potential KBAs for 13 species distributed throughout the Southern Ocean that were vital for each individual species, population, and life‐history stage for which they were determined. These areas were identified as highly used by these populations based on observational data and complement the ongoing habitat modeling and bioregionalization work that has been used to prioritize conservation areas in this region. Although further work is needed to identify potential KBAs based on additional current and future data sets, we highlight the benefits of utilizing KBAs as part of a holistic approach to marine conservation, given their significant value as a global conservation tool.

Occurrence, characterization, and ecological risk analysis of petroleum hydrocarbons in water and sediments following large-scale field simulated oil spills at the experimental lakes area, Northwestern Ontario, Canada - Zeyu Yang; Keval Shah; Bruce Hollebone; Sonia Laforest; Madison MacGillivray; Diane Dey; Jose Luis Rodriguez; Benoit Lalonde; Chun Yang; Vanessa Beaulac; Jules M. Blais; Mark Hanson; et al. (Marine Pollution Bulletin, 2024)

Measurement and modelling of water flows and pesticide leaching under low input cropping systems - Laure Mamy; Jesús M. Marín-Benito; Lionel Alletto; Eric Justes; Marjorie Ubertosi; Nicolas Munier-Jolain; Bernard Nicolardot; Catherine Bonnet; Julien Moeys; Mats Larsbo; Valérie Pot; Carole Bedos; et al. (Science of The Total Environment, 2024)

Trends and Variability in Earth’s Energy Imbalance and Ocean Heat Uptake Since 2005 - Maria Z. Hakuba; Sébastien Fourest; Tim Boyer; Benoit Meyssignac; James A. Carton; Gaël Forget; Lijing Cheng; Donata Giglio; Gregory C. Johnson; Seiji Kato; Rachel E. Killick; Nicolas Kolodziejczyk; et al. (Surveys in Geophysics, 2024)
Earth’s energy imbalance (EEI) is a fundamental metric of global Earth system change, quantifying the cumulative impact of natural and anthropogenic radiative forcings and feedback. To date, the most precise measurements of EEI change are obtained through radiometric observations at the top of the atmosphere (TOA), while the quantification of EEI absolute magnitude is facilitated through heat inventory analysis, where ~ 90% of heat uptake manifests as an increase in ocean heat content (OHC). Various international groups provide OHC datasets derived from in situ and satellite observations, as well as from reanalyses ingesting many available observations. The WCRP formed the GEWEX-EEI Assessment Working Group to better understand discrepancies, uncertainties and reconcile current knowledge of EEI magnitude, variability and trends. Here, 21 OHC datasets and ocean heat uptake (OHU) rates are intercompared, providing OHU estimates ranging between 0.40 ± 0.12 and 0.96 ± 0.08 W m −2 (2005–2019), a spread that is slightly reduced when unequal ocean sampling is accounted for, and that is largely attributable to differing source data, mapping methods and quality control procedures. The rate of increase in OHU varies substantially between − 0.03 ± 0.13 (reanalysis product) and 1.1 ± 0.6 W m −2 dec −1 (satellite product). Products that either more regularly observe (satellites) or fill in situ data-sparse regions based on additional physical knowledge (some reanalysis and hybrid products) tend to track radiometric EEI variability better than purely in situ-based OHC products. This paper also examines zonal trends in TOA radiative fluxes and the impact of data gaps on trend estimates. The GEWEX-EEI community aims to refine their assessment studies, to forge a path toward best practices, e.g., in uncertainty quantification, and to formulate recommendations for future activities.

Observational Assessment of Changes in Earth’s Energy Imbalance Since 2000 - Norman G. Loeb; Seung-Hee Ham; Richard P. Allan; Tyler J. Thorsen; Benoit Meyssignac; Seiji Kato; Gregory C. Johnson; John M. Lyman (Surveys in Geophysics, 2024)
Satellite observations from the Clouds and the Earth’s Radiant Energy System show that Earth’s energy imbalance has doubled from 0.5 ± 0.2 Wm −2 during the first 10 years of this century to 1.0 ± 0.2 Wm − 2 during the past decade. The increase is the result of a 0.9 ± 0.3 Wm −2 increase absorbed solar radiation (ASR) that is partially offset by a 0.4 ± 0.25 Wm −2 increase in outgoing longwave radiation (OLR). Despite marked differences in ASR and OLR trends during the hiatus (2000–2010), transition-to-El Niño (2010–2016) and post-El Niño (2016–2022) periods, trends in net top-of-atmosphere flux (NET) remain within 0.1 Wm −2 per decade of one another, implying a steady acceleration of climate warming. Northern and southern hemisphere trends in NET are consistent to 0.06 ± 0.31 Wm −2 per decade due to a compensation between weak ASR and OLR hemispheric trend differences of opposite sign. We find that large decreases in stratocumulus and middle clouds over the sub-tropics and decreases in low and middle clouds at mid-latitudes are the primary reasons for increasing ASR trends in the northern hemisphere (NH). These changes are especially large over the eastern and northern Pacific Ocean, and coincide with large increases in sea-surface temperature (SST). The decrease in cloud fraction and higher SSTs over the NH sub-tropics lead to a significant increase in OLR from cloud-free regions, which partially compensate for the NH ASR increase. Decreases in middle cloud reflection and a weaker reduction in low-cloud reflection account for the increase in ASR in the southern hemisphere, while OLR changes are weak. Changes in cloud cover in response to SST increases imply a feedback to climate change yet a contribution from radiative forcing or internal variability cannot be ruled out.

Rainfall during multiyear La Niñas caused the decline of social wasps in Northeastern Amazonia - Alain Dejean; Vivien Rossi; Arthur Compin; Bruno Corbara; James M. Carpenter; Jérôme Orivel; Frédéric Petitclerc; Benoit Burban; Frédéric Azémar (Ecology, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Testing the deep‐sea glacial disturbance hypothesis as a cause of low, present‐day Norwegian Sea diversity and resulting steep latitudinal diversity gradient, using fossil records - Anna B. Jöst; Huai‐Hsuan M. Huang; Yuanyuan Hong; Chih‐Lin Wei; Henning A. Bauch; Benoit Thibodeau; Thomas M. Cronin; Hisayo Okahashi; Moriaki Yasuhara (Global Ecology and Biogeography, 2024)
Aim Within the intensively‐studied, well‐documented latitudinal diversity gradient, the deep‐sea biodiversity of the present‐day Norwegian Sea stands out with its notably low diversity, constituting a steep latitudinal diversity gradient in the North Atlantic. The reason behind this has long been a topic of debate and speculation. Most prominently, it is explained by the deep‐sea glacial disturbance hypothesis, which states that harsh environmental glacial conditions negatively impacted Norwegian Sea diversities, which have not yet fully recovered. Our aim is to empirically test this hypothesis. Specific research questions are: (1) Has deep‐sea biodiversity been lower during glacials than during interglacials? ( 2) Was there any faunal shift at the Mid‐Brunhes Event (MBE) when the mode of glacial–interglacial climatic change was altered? Location Norwegian Sea, deep sea (1819–2800 m), coring sites MD992277, PS1243, and M23352. Time period 620.7–1.4 ka (Middle Pleistocene–Late Holocene). Taxa studied Ostracoda (Crustacea). Methods We empirically test the deep‐sea glacial disturbance hypothesis by investigating whether diversity in glacial periods is consistently lower than diversity in interglacial periods. Additionally, we apply comparative analyses to determine a potential faunal shift at the MBE, a Pleistocene event describing a fundamental shift in global climate. Results The deep Norwegian Sea diversity was not lower during glacial periods compared to interglacial periods. Holocene diversity was exceedingly lower than that of the last glacial period. Faunal composition changed substantially between pre‐ and post‐MBE. Main conclusions These results reject the glacial disturbance hypothesis, since the low glacial diversity is the important precondition here. The present‐day‐style deep Norwegian Sea ecosystem was established by the MBE, more specifically by MBE‐induced changes in global climate, which has led to more dynamic post‐MBE conditions. In a broader context, this implies that the MBE has played an important role in the establishment of the modern polar deep‐sea ecosystem and biodiversity in general.

Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Daijun Liu; Franz Essl; Bernd Lenzner; Dietmar Moser; Philipp Semenchuk; Tim M. Blackburn; Phillip Cassey; Dino Biancolini; César Capinha; Wayne Dawson; Ellie E. Dyer; Benoit Guénard; et al. (Global Change Biology, 2024)
The ecological impact of non‐native species arises from their establishment in local assemblages. However, the rates of non‐native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non‐native species and residence of non‐native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non‐native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non‐native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi‐natural ecosystems. Notably, non‐native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land‐use types rather than croplands and urban areas. The impact of residence time on non‐native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land‐use types. The unpredictability of future impacts, implied by the slow spread of non‐native species, strengthens the call for stronger regulations on the exchange of non‐native species to reduce the long‐lasting invasion debt looming on ecosystems' future.

Improved large-area forest increment information in Europe through harmonisation of National Forest Inventories - Thomas Gschwantner; Thomas Riedel; Lea Henning; Patricia Adame; Radim Adolt; Ana Aguirre; Iciar Alberdi; Valerio Avitabile; Isabel Cañellas; Lucio Di Cosmo; Christoph Fischer; Alexandra Freudenschuß; et al. (Forest Ecology and Management, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Formation and evolution of metapelitic-derived melts within anatectic complexes: Geochemical constraints and inferences on the protoliths and geodynamics of the Porto-Viseu Metamorphic Belt, Central Iberian Zone (central-north Portugal) - B. Cotrim; T. Bento dos Santos; M.R. Azevedo; P. Cachapuz; D. Carvalho; M. Benoit (Geochemistry, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Automatic detection of airborne pollen: an overview - Jeroen Buters; Bernard Clot; Carmen Galán; Regula Gehrig; Stefan Gilge; François Hentges; David O’Connor; Branko Sikoparija; Carsten Skjoth; Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; et al. (Aerobiologia, 2024)
Pollen monitoring has traditionally been carried out using manual methods first developed in the early 1950s. Although this technique has been recently standardised, it suffers from several drawbacks, notably data usually only being available with a delay of 3–9 days and usually delivered at a daily resolution. Several automatic instruments have come on to the market over the past few years, with more new devices also under development. This paper provides a comprehensive overview of all available and developing automatic instruments, how they measure, how they identify airborne pollen, what impacts measurement quality, as well as what potential there is for further advancement in the field of bioaerosol monitoring.

Coral carbonate-bound isotopes reveal monsoonal influence on nitrogen sources in Southeastern China's Greater Bay Area from the mid-Holocene until the Anthropocene - Jonathan D. Cybulski; Nicolas N. Duprey; Benoit Thibodeau; Moriaki Yasuhara; Naomi Geeraert; Nicole Leonard; Hubert B. Vonhof; Alfredo Martínez-García; David M. Baker (Marine Pollution Bulletin, 2023)

Use of atmospheric tides to estimate the hydraulic conductivity of confined and semi-confined aquifers - Rémi Valois; Benoit Derode; Jean-Michel Vouillamoz; D. O. Valerie Kotchoni; M. A. Lawson; Gabriel C. Rau (Hydrogeology Journal, 2023)

Brain metabolite levels in remitted psychotic depression with consideration of effects of antipsychotic medication - Hideaki Tani; Iska Moxon-Emre; Natalie J. Forde; Nicholas H. Neufeld; Kathleen S. Bingham; Ellen M. Whyte; Barnett S. Meyers; George S. Alexopoulos; Matthew J. Hoptman; Anthony J. Rothschild; Hiroyuki Uchida; Alastair J. Flint; et al. (Brain Imaging and Behavior, 2023)
Background The neurobiology of psychotic depression is not well understood and can be confounded by antipsychotics. Magnetic resonance spectroscopy (MRS) is an ideal tool to measure brain metabolites non-invasively. We cross-sectionally assessed brain metabolites in patients with remitted psychotic depression and controls. We also longitudinally assessed the effects of olanzapine versus placebo on brain metabolites. Methods Following remission, patients with psychotic depression were randomized to continue sertraline + olanzapine ( n = 15) or switched to sertraline + placebo ( n = 18), at which point they completed an MRS scan. Patients completed a second scan either 36 weeks later, relapse, or discontinuation. Where water-scaled metabolite levels were obtained and a Point-RESolved Spectroscopy sequence was utilized, choline, myo-inositol, glutamate + glutamine (Glx), N -acetylaspartate, and creatine were measured in the left dorsolateral prefrontal cortex (L-DLPFC) and dorsal anterior cingulate cortex (dACC). An ANCOVA was used to compare metabolites between patients ( n = 40) and controls ( n = 46). A linear mixed-model was used to compare olanzapine versus placebo groups. Results Cross-sectionally, patients (compared to controls) had higher myo-inositol (standardized mean difference [SMD] = 0.84; 95%CI = 0.25–1.44; p = 0.005) in the dACC but not different Glx, choline, N -acetylaspartate, and creatine. Longitudinally, patients randomized to placebo (compared to olanzapine) showed a significantly greater change with a reduction of creatine (SMD = 1.51; 95%CI = 0.71–2.31; p = 0.0002) in the dACC but not glutamate + glutamine, choline, myo-inositol, and N -acetylaspartate. Conclusions Patients with remitted psychotic depression have higher myo-inositol than controls. Olanzapine may maintain creatine levels. Future studies are needed to further disentangle the mechanisms of action of olanzapine.

Treated and highly diluted, but wastewater still impacts diversity and energy fluxes of freshwater food webs - Ioar de Guzman; Arturo Elosegi; Daniel von Schiller; Jose M. González; Laura E. Paz; Benoit Gauzens; Ulrich Brose; Alvaro Antón; Nuria Olarte; José M. Montoya; Aitor Larrañaga (Journal of Environmental Management, 2023)

Obesity promotes fumonisin B1 hepatotoxicity - Léonie Dopavogui; Marion Régnier; Arnaud Polizzi; Quentin Ponchon; Sarra Smati; Wendy Klement; Frédéric Lasserre; Céline Lukowicz; Yannick Lippi; Anne Fougerat; Justine Bertrand-Michel; Claire Naylies; et al. (Science of The Total Environment, 2023)

Predictors of Dairy Worker Pre-Test and Post-Test Performance on a Dairy Safety Knowledge Test: Impact of Education Level and Native Language - M Benoit; E Austin; N Simcox; P Rabinowitz; M Yost (Journal of Agromedicine, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

PERMANOVA testing and Poisson Log-Normal modelling unravel how two traditional cheeses are distinguished through sorting and verbalization tasks - P.-M. Grollemund; L. Lenoir; J. Benoit; C. Chassard; C. Bord (Food Quality and Preference, 2023)

Geographic and climatic constraints on bioregionalization of European ants - Runxi Wang; Jamie M. Kass; Christophe Galkowski; Federico Garcia; Matthew T. Hamer; Alexander Radchenko; Sebastian D. Salata; Enrico Schifani; Zalimkhan M. Yusupov; Evan P. Economo; Benoit Guénard (Journal of Biogeography, 2023)
Aim Biogeographical regionalization is scant for most insect groups due to shortfalls in distribution and phylogenetic information, namely the Wallacean and Darwinian shortfalls respectively. Here, we focused on the European ants and compared new techniques to classical analyses based on regional lists and taxonomic methods. We asked the following: (1) Can grid‐based regionalizations using novel distribution data improve biogeographical transitions? and (2) Can phylogenetic approaches reveal new insights regarding ant evolutionary history? Location Europe and Anatolia. Taxon Ants (Formicidae). Methods First, we developed a refined database integrating the occurrences of 747 ant species across 207 regions of Europe and Anatolia, based on newly expert‐validated records derived from the existing Global Ant Biodiversity Informatics database. Using range estimates for these species derived from polygons and species distribution modelling, we produced species assemblages in 50 × 50 km grid cells. We calculated taxonomic and phylogenetic turnover of ant assemblages, then performed a hierarchical clustering procedure to delineate biogeographical structure. Results At both the regional list and grid assemblage levels, the Mediterranean has higher turnover and more biogeographical regions than northern Europe, both taxonomically and phylogenetically. Delineations based on grid assemblages detected more detailed biogeographical transitions, while those based on regional lists showed stronger insularity in biogeographical structure. The phylogenetic regionalization suggested a very similar spatial structure but varied affinities between assemblages in comparison to the taxonomic approach. Main Conclusions Here, we integrated expert‐validated regional lists, species distribution modelling and a recent phylogeny to tackle Wallacean and Darwinian shortfalls for an important insect group by developing a next‐generation map of biogeographical regionalization for European ants. The results of this study suggest strong constraints from geographical barriers and potential effects of climatic history on ant distributions and evolutionary history, and also provide baseline spatial information for future investigations of regional insect distributions.

High-frequency sequence stratigraphy of Pennsylvanian-Lower Permian carbonate successions of the Robledo Mountains, New Mexico and the Carnic Alps, Austria: a record of the acme and demise of the late Palaeozoic ice age - Daniel Calvo González; Benoit Beauchamp; Charles M. Henderson (Facies, 2023)

Late Cenozoic environmental changes drove the diversification of a weevil genus endemic to the Cape Floristic Region - Noémie M.‐C. Hévin; Steffan Hansen; Pia Addison; Laure Benoit; Gael J. Kergoat; Julien Haran (Zoologica Scripta, 2022)
The Cape Floristic Region in the Republic of South Africa is a well‐recognized hotspot of biodiversity. Although this region is mostly known for its high level of plant diversity and endemicity, it also hosts an understudied and likely diverse arthropod fauna. Here we investigate the evolutionary history and timing of diversification of the apterous weevil genus Phlyctinus (Curculionidae: Entiminae), which is endemic to the coastal area and adjacent mountain ranges of the Cape floristic region and generally associated with sunflower plants (Asteraceae). We use a diverse array of molecular analyses (phylogenetic inference, molecular species delimitation and dating analyses) to analyse a novel molecular dataset of 202 weevil specimens (including 170 Phlyctinus sampled in 60 sites), and sequenced for two mitochondrial and four nuclear gene fragments. Phylogenetic and dating analyses indicate that the genus started diversifying in the late Miocene, with contrasting diversification dynamics for the three inferred clades, which present disjunct distributions. Host plant records and the lack of relatedness of species living in sympatry indicate that the diversification of Phlyctinus was predominantly driven by allopatric (geographic) speciation. We hypothesize that the interplay between topography and recurring cycles of coastline‐habitat fragmentation resulting from sea level oscillations spurred the diversification of the most speciose clade, whereas in the two remaining clades populations likely remained connected thus hampering allopatric speciation. Interestingly, this pattern echoes with the role of sea level oscillations as an important driver of the radiation of several lineages in the coastline ecosystems of the Cape Floristic Region.

Oceanic giants dance to atmospheric rhythms: Ephemeral wind‐driven resource tracking by blue whales - John P. Ryan; Kelly J. Benoit‐Bird; William K. Oestreich; Paul Leary; Kevin B. Smith; Chad M. Waluk; David E. Cade; James A. Fahlbusch; Brandon L. Southall; John E. Joseph; Tetyana Margolina; John Calambokidis; et al. (Ecology Letters, 2022)
Trophic transfer of energy through marine food webs is strongly influenced by prey aggregation and its exploitation by predators. Rapid aggregation of some marine fish and crustacean forage species during wind‐driven coastal upwelling has recently been discovered, motivating the hypothesis that predators of these forage species track the upwelling circulation in which prey aggregation occurs. We examine this hypothesis in the central California Current Ecosystem using integrative observations of upwelling dynamics, forage species' aggregation, and blue whale movement. Directional origins of blue whale calls repeatedly tracked upwelling plume circulation when wind‐driven upwelling intensified and aggregation of forage species was heightened. Our findings illustrate a resource tracking strategy by which blue whales may maximize energy gain amid ephemeral foraging opportunities. These findings have implications for the ecology and conservation of diverse predators that are sustained by forage populations whose behaviour is responsive to episodic environmental dynamics.

Genome of elegance coral Catalaphyllia jardinei (Euphylliidae) - Yifei Yu; Wenyan Nong; Wai Lok So; Yichun Xie; Ho Yin Yip; Jasmine Haimovitz; Thomas Swale; David M. Baker; William G. Bendena; Ting Fung Chan; Apple P. Y. Chui; Kwok Fai Lau; et al. (Frontiers in Marine Science, 2022)
Coral reefs are under stress throughout the world. To better understand the molecular mechanisms underlying coral biology and their genomic evolution, here we sequenced the genome and transcriptomes of elegance coral Catalaphyllia jardinei (Euphylliidae). This monotypic genus stony coral is widespread but rare, being found across the Indo-West Pacific, from the northern Indian Ocean, Australia, Philippines, to the South China Sea. Due to its popularity among aquarium hobbyists, it is an overexploited species collected in large quantities from the wild for aquarium trade. The assembled genome is ~ 651.3 Mb in total length and of high physical contiguity with a scaffold N50 size of 28.9 Mb. The gene copy numbers of abiotic stress regulator (heat shock protein family genes) and neuropeptides (GLWamide, GRFamide, PRGamide and HIRamide) are similar to other sequenced anthozoans, and we have also identified the first set of sesquiterpenoid biosynthetic pathway genes in coral. Sequencing of small RNAs allows us to identify 35 microRNAs in C. jardinei and update the number of conserved microRNAs in cnidarians. This study established a foundation for further investigation into the roles of sesquiterpenoids and microRNAs in development of coral and understand their responses to climate change. Due to the easiness to culture C. jardinei in reef tanks and the established resources in this study, we propose this species be adopted as a new laboratory model in environmental and ecological experiments aiming to understand coral biology and responses to environmental stressors.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Third-party vocal intervention in the proboscis monkey (Nasalis larvatus) - Marina Scheumann; Kathrin M. Röper; Senthilvel K. S. S. Nathan; Benoit Goossens (International Journal of Primatology, 2022)
Vocal intervention is a triadic social interaction, where a third party responds vocally to a conflict between group members, minimizing the costs of aggression in response to the intervention. Because there is little information on vocal third-party intervention in nonhuman mammals, we investigated whether adult male proboscis monkeys use the bray vocalization as a vocal third-party intervention signal to intervene in intragroup conflicts. First, we audio-recorded 1,811 vocalizations from 17 free-ranging proboscis monkey groups in the Lower Kinabatangan Wildlife Sanctuary, analyzing 378 vocal responses of the adult male to agonistic vocal exchanges (shrieks) of group members. Second, we video- and audio-recorded five habituated groups in the Labuk Bay Proboscis Monkey Sanctuary investigating the context of these vocalizations and the conflict dyads evoking vocal support. We found that adult males of one-male/multifemale groups mainly uttered bray vocalizations, whereas females, immatures, and infants uttered shrieks in intragroup conflicts or in response to other animal species. The adult male uttered significantly more often brays after agonistic shrieks than expected based on the overall occurrence of brays. Brays ended 65% of agonistic conflicts, which were accompanied by vocalizations of the conflict partners and occurred more often after conflicts between females than between offspring. This suggests that the bray functions as a vocal third-party intervention signal for intragroup conflict resolution. We suggest that living in the high canopies of the tropical rainforest might restrict direct access to conflict partners and prevent physical intervention, favoring the evolution of the bray as a third-party vocal intervention signal.

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Targeting Ni-Cu mineralization in the Canadian High Arctic large igneous province: integrating geochemistry, magmatic architecture and structure - Benoit M. Saumur; Marie-Claude Williamson; Jean H. Bédard (Mineralium Deposita, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Impact of net houses on the natural regulation of the populations of Trialeurodes vaporariorum (Homoptera: Aleyrodidae) and Tuta absoluta (Lepidoptera: Gelechiidae), two major tomato pests in Kenya - Anaïs Chailleux; Junitor Chepkemoi; Julien M. Haran; Laure Benoit; Robert Copeland; Emilie Deletre (International Journal of Tropical Insect Science, 2022)

Occupational rhinitis and asthma in bakers: a cross-sectional study in the former Katanga province of DR Congo - Joseph Pyana Kitenge; Paul Musa Obadia; Trésor Carsi Kuhangana; Tony Kayembe-Kitenge; Patient Nkulu Banza; Lilian Nsenga Mukanda; Pascal Nawej Tshimwang; Patrick D. M. C. Katoto; Celestin Banza Nkulu Lubaba; Abdon Mukalay wa Mukalay; Benoit Nemery (International Archives of Occupational and Environmental Health, 2022)

A sit‐and‐wait predator, but not an active‐pursuit predator, alters pollinator‐mediated selection on floral traits - Amanda D. Benoit; Christina M. Caruso (Ecology, 2021)
Indirect species interactions are ubiquitous in nature, often outnumbering direct species interactions. Yet despite evidence that indirect interactions have strong ecological effects, relatively little is known about whether they can shape adaptive evolution by altering the strength and/or direction of natural selection. We tested whether indirect interactions affect the strength and direction of pollinator‐mediated selection on floral traits of the bumble‐bee pollinated wildflower Lobelia siphilitica . We estimated the indirect effects of two pollinator predators with contrasting hunting modes: dragonflies (Aeshnidae and Corduliidae) and ambush bugs ( Phymata americana , Reduviidae). Because dragonflies are active pursuit predators, we hypothesized that they would strengthen pollinator‐mediated selection by weakening plant–pollinator interactions (i.e., a density‐mediated indirect effect). In contrast, because ambush bugs are sit‐and‐wait predators, we hypothesized that they would weaken or reverse the direction of pollinator‐mediated selection by altering pollinator foraging behavior (i.e., a trait‐mediated indirect effect). Specifically, if ambush bugs hunt from plants with traits that attract pollinators (i.e., prey), then pollinators will spend less time visiting those plants, weakening or reversing the direction of selection on attractive floral traits. We did not find evidence that high dragonfly abundance strengthened selection on floral traits via a density‐mediated indirect effect: neither pollen limitation (a proxy for the strength of plant–pollinator interactions) nor directional selection on floral traits of L. siphilitica differed significantly between high‐ and low‐dragonfly abundance treatments. In contrast, we did find evidence that ambush bug presence affected selection on floral traits via a trait‐mediated indirect effect: ambush bugs hunted from L. siphilitica plants with larger daily floral displays, reversing the direction of pollinator‐mediated selection on daily display size. These results suggest that indirect species interactions have the potential to shape adaptive evolution by altering natural selection.

Ocean Acidification Amplifies the Olfactory Response to 2-Phenylethylamine: Altered Cue Reception as a Mechanistic Pathway? - Paula Schirrmacher; Christina C. Roggatz; David M. Benoit; Jörg D. Hardege (Journal of Chemical Ecology, 2021)
With carbon dioxide (CO 2 ) levels rising dramatically, climate change threatens marine environments. Due to increasing CO 2 concentrations in the ocean, pH levels are expected to drop by 0.4 units by the end of the century. There is an urgent need to understand the impact of ocean acidification on chemical-ecological processes. To date, the extent and mechanisms by which the decreasing ocean pH influences chemical communication are unclear. Combining behaviour assays with computational chemistry, we explore the function of the predator related cue 2-phenylethylamine (PEA) for hermit crabs ( Pagurus bernhardus ) in current and end-of-the-century oceanic pH. Living in intertidal environments, hermit crabs face large pH fluctuations in their current habitat in addition to climate-change related ocean acidification. We demonstrate that the dietary predator cue PEA for mammals and sea lampreys is an attractant for hermit crabs, with the potency of the cue increasing with decreasing pH levels. In order to explain this increased potency, we assess changes to PEA’s conformational and charge-related properties as one potential mechanistic pathway. Using quantum chemical calculations validated by NMR spectroscopy, we characterise the different protonation states of PEA in water. We show how protonation of PEA could affect receptor-ligand binding, using a possible model receptor for PEA (human TAAR1). Investigating potential mechanisms of pH-dependent effects on olfactory perception of PEA and the respective behavioural response, our study advances the understanding of how ocean acidification interferes with the sense of smell and thereby might impact essential ecological interactions in marine ecosystems.

Juvenile corals underpin coral reef carbonate production after disturbance - Jérémy Carlot; Mohsen Kayal; Hunter S. Lenihan; Simon J. Brandl; Jordan M. Casey; Mehdi Adjeroud; Ulisse Cardini; Alexandre Merciere; Benoit Espiau; Diego R. Barneche; Alessio Rovere; Laetitia Hédouin; et al. (Global Change Biology, 2021)
Sea‐level rise is predicted to cause major damage to tropical coastlines. While coral reefs can act as natural barriers for ocean waves, their protection hinges on the ability of scleractinian corals to produce enough calcium carbonate (CaCO 3 ) to keep up with rising sea levels. As a consequence of intensifying disturbances, coral communities are changing rapidly, potentially reducing community‐level CaCO 3 production. By combining colony‐level physiology and long‐term monitoring data, we show that reefs recovering from major disturbances can produce 40% more CaCO 3 than currently estimated due to the disproportionate contribution of juvenile corals. However, the buffering effect of highly productive juvenile corals is compromised by recruitment failures, which have been more frequently observed after large‐scale, repeated bleaching events. While the size structure of corals can bolster a critical ecological function on reefs, climate change impacts on recruitment may undermine this buffering effect, thus further compromising the persistence of reefs and their provision of important ecosystem services.

Seeing through the static: the temporal dimension of plant–animal mutualistic interactions - Paul J. CaraDonna; Laura A. Burkle; Benjamin Schwarz; Julian Resasco; Tiffany M. Knight; Gita Benadi; Nico Blüthgen; Carsten F. Dormann; Qiang Fang; Jochen Fründ; Benoit Gauzens; Christopher N. Kaiser‐Bunbury; et al. (Ecology Letters, 2021)
Most studies of plant–animal mutualistic networks have come from a temporally static perspective. This approach has revealed general patterns in network structure, but limits our ability to understand the ecological and evolutionary processes that shape these networks and to predict the consequences of natural and human‐driven disturbance on species interactions. We review the growing literature on temporal dynamics of plant–animal mutualistic networks including pollination, seed dispersal and ant defence mutualisms. We then discuss potential mechanisms underlying such variation in interactions, ranging from behavioural and physiological processes at the finest temporal scales to ecological and evolutionary processes at the broadest. We find that at the finest temporal scales (days, weeks, months) mutualistic interactions are highly dynamic, with considerable variation in network structure. At intermediate scales (years, decades), networks still exhibit high levels of temporal variation, but such variation appears to influence network properties only weakly. At the broadest temporal scales (many decades, centuries and beyond), continued shifts in interactions appear to reshape network structure, leading to dramatic community changes, including loss of species and function. Our review highlights the importance of considering the temporal dimension for understanding the ecology and evolution of complex webs of mutualistic interactions.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Supplementing selection decisions in a hybrid wheat breeding program by using F2 yield as a proxy of F1 performance - Anil Adhikari; Amir M. H. Ibrahim; Jackie C. Rudd; P. Stephen Baenziger; Amanda Easterly; Nick Garst; Vikas Belamkar; Jean-Benoit Sarazin (Euphytica, 2020)

Forecasting intensifying disturbance effects on coral reefs - Julie Vercelloni; Benoit Liquet; Emma V. Kennedy; Manuel González‐Rivero; M. Julian Caley; Erin E. Peterson; Marji Puotinen; Ove Hoegh‐Guldberg; Kerrie Mengersen (Global Change Biology, 2020)
Anticipating future changes of an ecosystem's dynamics requires knowledge of how its key communities respond to current environmental regimes. The Great Barrier Reef (GBR) is under threat, with rapid changes of its reef‐building hard coral (HC) community structure already evident across broad spatial scales. While several underlying relationships between HC and multiple disturbances have been documented, responses of other benthic communities to disturbances are not well understood. Here we used statistical modelling to explore the effects of broad‐scale climate‐related disturbances on benthic communities to predict their structure under scenarios of increasing disturbance frequency. We parameterized a multivariate model using the composition of benthic communities estimated by 145,000 observations from the northern GBR between 2012 and 2017. During this time, surveyed reefs were variously impacted by two tropical cyclones and two heat stress events that resulted in extensive HC mortality. This unprecedented sequence of disturbances was used to estimate the effects of discrete versus interacting disturbances on the compositional structure of HC, soft corals (SC) and algae. Discrete disturbances increased the prevalence of algae relative to HC while the interaction between cyclones and heat stress was the main driver of the increase in SC relative to algae and HC. Predictions from disturbance scenarios included relative increases in algae versus SC that varied by the frequency and types of disturbance interactions. However, high uncertainty of compositional changes in the presence of several disturbances shows that responses of algae and SC to the decline in HC needs further research. Better understanding of the effects of multiple disturbances on benthic communities as a whole is essential for predicting the future status of coral reefs and managing them in the light of new environmental regimes. The approach we develop here opens new opportunities for reaching this goal.

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Using genomic data to develop SSR markers for species of Chresta (Vernonieae, Asteraceae) from the Caatinga - Carolina M. Siniscalchi; Benoit Loeuille; José R. Pirani; Jennifer R. Mandel (Brazilian Journal of Botany, 2019)

Guest Editorial: Relationships Between Coastal Sea Level and Large-Scale Ocean Circulation - Rui M. Ponte; Benoit Meyssignac; Catia M. Domingues; Detlef Stammer; Anny Cazenave; Teodolina Lopez (Surveys in Geophysics, 2019)

Precipitation mediates sap flux sensitivity to evaporative demand in the neotropics - Charlotte Grossiord; Bradley Christoffersen; Aura M. Alonso-Rodríguez; Kristina Anderson-Teixeira; Heidi Asbjornsen; Luiza Maria T. Aparecido; Z. Carter Berry; Christopher Baraloto; Damien Bonal; Isaac Borrego; Benoit Burban; Jeffrey Q. Chambers; et al. (Oecologia, 2019)

The neutrophil to lymphocyte ratio indexes individual variation in the behavioural stress response of wild roe deer across fluctuating environmental conditions - Jeffrey Carbillet; Benjamin Rey; Typhaine Lavabre; Yannick Chaval; Joël Merlet; François Débias; Corinne Régis; Sylvia Pardonnet; Jeanne Duhayer; Jean-Michel Gaillard; A. J. M. Hewison; Jean-François Lemaître; et al. (Behavioral Ecology and Sociobiology, 2019)

LRP1 Has a Predominant Role in Production over Clearance of Aβ in a Mouse Model of Alzheimer’s Disease - Bart Van Gool; Steffen E. Storck; Sara M. Reekmans; Benoit Lechat; Philip L. S. M. Gordts; Laurent Pradier; Claus U. Pietrzik; Anton J. M. Roebroek (Molecular Neurobiology, 2019)

Genetic Mapping of Steroidal Glycoalkaloids Using Selective Genotyping in Potato - Jamuna Risal Paudel; Kyle M. Gardner; Benoit Bizimungu; David De Koeyer; Jun Song; Helen H. Tai (American Journal of Potato Research, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Variation of isotope composition in kelps from Kongsfjorden (Svalbard) - Cornelia M. Buchholz; Benoit Lebreton; Inka Bartsch; Christian Wiencke (Marine Biology, 2019)

Frontiers in Fine-Scale in situ Studies: Opportunities During the SWOT Fast Sampling Phase - Francesco d’Ovidio; Ananda Pascual; Jinbo Wang; Andrea M. Doglioli; Zhao Jing; Sebastien Moreau; Gérald Grégori; Sebastiaan Swart; Sabrina Speich; Frédéric Cyr; Benoit Legresy; Yi Chao; et al. (Frontiers in Marine Science, 2019)

Globally Consistent Quantitative Observations of Planktonic Ecosystems - Fabien Lombard; Emmanuel Boss; Anya M. Waite; Meike Vogt; Julia Uitz; Lars Stemmann; Heidi M. Sosik; Jan Schulz; Jean-Baptiste Romagnan; Marc Picheral; Jay Pearlman; Mark D. Ohman; et al. (Frontiers in Marine Science, 2019)

JOHN UTTING (1940–2018) - James M. White; Jennifer Galloway; Gunn Mangerud; Benoit Beauchamp (Palynology, 2019)

Evolution of the latitudinal diversity gradient in the hyperdiverse ant genus Pheidole - Evan P. Economo; Jen‐Pan Huang; Georg Fischer; Eli M. Sarnat; Nitish Narula; Milan Janda; Benoit Guénard; John T. Longino; L. Lacey Knowles (Global Ecology and Biogeography, 2019)
Aim The latitudinal diversity gradient is the dominant geographic pattern of life on Earth, but a consensus understanding of its origins has remained elusive. The analysis of recently diverged, hyper‐rich invertebrate groups provides an opportunity to investigate latitudinal patterns with the statistical power of large trees while minimizing potentially confounding variation in ecology and history. Here, we synthesize global phylogenetic and macroecological data on a hyperdiverse (> 1,100 species) ant radiation, Pheidole and test predictions of three general explanations for the latitudinal gradient: variation in diversification rates, tropical conservatism and ecological regulation. Location Global. Time period The past 35 million years. Major taxa studied The hyperdiverse ant genus Pheidole Westwood. Methods We assembled geographic data for 1,499 species and morphospecies, and inferred a dated phylogeny for 449 species of Pheidole , including 167 species newly sequenced for this study. We tested for correlations between diversification rate and latitude with Bayesian analysis of macroevolutionary mixtures (BAMM), hidden state speciation and extinction (HiSSE), geographic state speciation and extinction (GeoSSE), and a non‐parametric method (FiSSE), evaluated evidence for richness steady state, and examined patterns of diversification as Pheidole spread around the globe. Results There was no evidence of systematic variation of net diversification rates with latitude across any of the methods. We found that Pheidole diversification occurred in bursts when new continents were colonized, followed by a slowdown in each region, but there is no evidence richness has saturated at an equilibrium in any region. Additionally, we found latitudinal affinity is moderately conserved with a Neotropical ancestor and simulations show that phylogenetic inertia alone is sufficient to produce the gradient pattern. Main conclusions Our results provide no evidence that diversification rates vary systematically with latitude. Richness is far from steady state in each region, contrary to the ecological regulation hypothesis, although there is evidence that ecological opportunity promotes diversification after colonization of new areas. The fact that niche conservatism is strong enough to produce the gradient pattern is in accord with the tropical conservatism hypothesis. Overall, these results shed light on the mechanisms underlying the emergence of the diversity gradient within the past 34 million years, complementing recent work on deeper time‐scales, and more generally contribute toward much‐needed invertebrate perspective on global biodiversity dynamics.

Hippocampal LTP modulation and glutamatergic receptors following vestibular loss - B. Truchet; A. Benoit; F. Chaillan; P. F. Smith; B. Philoxene; M. Guillamin; B. Poucet; A. Coquerel; Stephane Besnard (Brain Structure and Function, 2019)

Manipulating host resistance structure reveals impact of pathogen dispersal and environmental heterogeneity on epidemics - Rachel M. Penczykowski; Steven R. Parratt; Benoit Barrès; Suvi K. Sallinen; Anna‐Liisa Laine (Ecology, 2018)
Understanding how variation in hosts, parasites, and the environment shapes patterns of disease is key to predicting ecological and evolutionary outcomes of epidemics. Yet in spatially structured populations, variation in host resistance may be spatially confounded with variation in parasite dispersal and environmental factors that affect disease processes. To tease apart these disease drivers, we paired surveys of natural epidemics with experiments manipulating spatial variation in host susceptibility to infection. We mapped epidemics of the wind‐dispersed powdery mildew pathogen Podosphaera plantaginis in five populations of its plant host, Plantago lanceolata . At 15 replicate sites within each population, we deployed groups of healthy potted ‘sentinel’ plants from five allopatric host lines. By tracking which sentinels became infected in the field and measuring pathogen connectivity and microclimate at those sites, we could test how variation in these factors affected disease when spatial variation in host resistance and soil conditions was minimized. We found that the prevalence and severity of sentinel infection varied over small spatial scales in the field populations, largely due to heterogeneity in pathogen prevalence on wild plants and unmeasured environmental factors. Microclimate was critical for disease spread only at the onset of epidemics, where humidity increased infection risk. Sentinels were more likely to become infected than initially healthy wild plants at a given field site. However, in a follow‐up laboratory inoculation study we detected no significant differences between wild and sentinel plant lines in their qualitative susceptibility to pathogen isolates from the field populations, suggesting that primarily non‐genetic differences between sentinel and wild hosts drove their differential infection rates in the field. Our study leverages a multi‐faceted experimental approach to disentangle important biotic and abiotic drivers of disease patterns within wild populations.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Cold Water in a Warm World: Investigating the Origin of the Nordic Seas' Unique Surface Properties During MIS 11 - John M. Doherty; Benoit Thibodeau (Frontiers in Marine Science, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Response to Editor to the comment by Schipper & Smith to our paper entitled “Continuous soil carbon storage of old permanent pastures in Amazonia” - Sébastien Fontaine; Clément Stahl; Katja Klumpp; Catherine Picon‐Cochard; Marcia M. Grise; Camille Dezécache; Lise Ponchant; Vincent Freycon; Lilian Blanc; Damien Bonal; Benoit Burban; Jean‐François Soussana; et al. (Global Change Biology, 2018)

Mind the cell: Seasonal variation in telomere length mirrors changes in leucocyte profile - Michaël Beaulieu; Laure Benoit; Steven Abaga; Peter M. Kappeler; Marie J. E. Charpentier (Molecular Ecology, 2017)
Leucocytes are typically considered as a whole in studies examining telomere dynamics in mammals. Such an approach may be precarious, as leucocytes represent the only nucleated blood cells in mammals, their composition varies temporally, and telomere length differs between leucocyte types. To highlight this limitation, we examined here whether seasonal variation in leucocyte composition was related to variation in telomere length in free‐ranging mandrills ( Mandrilllus sphinx ). We found that the leucocyte profile of mandrills varied seasonally, with lower lymphocyte proportion being observed during the long dry season presumably because of the combined effects of high nematode infection and stress at that time of the year. Interestingly, this low lymphocyte proportion during the long dry season was associated with shorter telomeres. Accordingly, based on longitudinal data, we found that seasonal changes in lymphocyte proportion were reflected by corresponding seasonal variation in telomere length. Overall, these results suggest that variation in lymphocyte proportion in blood can significantly affect telomere measurements in mammals. However, lymphocyte proportion did not entirely explain variation in telomere length. For instance, a lower lymphocyte proportion with age could not fully explain shorter telomeres in older individuals. Overall, our results show that telomere length and leucocyte profile are strongly although imperfectly intertwined, which may obscure the relationship between telomere dynamics and ageing processes in mammals.

Virus-induced gene silencing of the two squalene synthase isoforms of apple tree (Malus × domestica L.) negatively impacts phytosterol biosynthesis, plastid pigmentation and leaf growth - Sandra M. Navarro Gallón; Carolina Elejalde-Palmett; Dimitri Daudu; Franziska Liesecke; Frédéric Jullien; Nicolas Papon; Thomas Dugé de Bernonville; Vincent Courdavault; Arnaud Lanoue; Audrey Oudin; Gaëlle Glévarec; Olivier Pichon; et al. (Planta, 2017)

Local adaptation at higher trophic levels: contrasting hyperparasite–pathogen infection dynamics in the field and laboratory - Steven R. Parratt; Benoit Barrès; Rachel M. Penczykowski; Anna‐Liisa Laine (Molecular Ecology, 2017)
Predicting and controlling infectious disease epidemics is a major challenge facing the management of agriculture, human and wildlife health. Co‐evolutionarily derived patterns of local adaptation among pathogen populations have the potential to generate variation in disease epidemiology; however, studies of local adaptation in disease systems have mostly focused on interactions between competing pathogens or pathogens and their hosts. In nature, parasites and pathogens are also subject to attack by hyperparasitic natural enemies that can severely impact upon their infection dynamics. However, few studies have investigated whether this interaction varies across combinations of pathogen–hyperparasite strains, and whether this influences hyperparasite incidence in natural pathogen populations. Here, we test whether the association between a hyperparasitic fungus, Ampelomyces, and a single powdery mildew host, Podosphaera plantaginis, varies among genotype combinations, and whether this drives hyperparasite incidence in nature. Laboratory inoculation studies reveal that genotype, genotype × genotype interactions and local adaptation affect hyperparasite infection. However, observations of a natural pathogen metapopulation reveal that spatial rather than genetic factors predict the risk of hyperparasite presence. Our results highlight how sensitive the outcome of biocontrol using hyperparasites is to selection of hyperparasite strains.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Observed volatilization fluxes of S-metolachlor and benoxacor applied on soil with and without crop residues - C. Bedos; L. Alletto; B. Durand; O. Fanucci; A. Brut; M. Bourdat-Deschamps; S. Giuliano; B. Loubet; E. Ceschia; P. Benoit (Environmental Science and Pollution Research, 2017)

Ocean acidification affects marine chemical communication by changing structure and function of peptide signalling molecules - Christina C. Roggatz; Mark Lorch; Jörg D. Hardege; David M. Benoit (Global Change Biology, 2016)
Ocean acidification is a global challenge that faces marine organisms in the near future with a predicted rapid drop in pH of up to 0.4 units by the end of this century. Effects of the change in ocean carbon chemistry and pH on the development, growth and fitness of marine animals are well documented. Recent evidence also suggests that a range of chemically mediated behaviours and interactions in marine fish and invertebrates will be affected. Marine animals use chemical cues, for example, to detect predators, for settlement, homing and reproduction. But, while effects of high CO 2 conditions on these behaviours are described across many species, little is known about the underlying mechanisms, particularly in invertebrates. Here, we investigate the direct influence of future oceanic pH conditions on the structure and function of three peptide signalling molecules with an interdisciplinary combination of methods. NMR spectroscopy and quantum chemical calculations were used to assess the direct molecular influence of pH on the peptide cues, and we tested the functionality of the cues in different pH conditions using behavioural bioassays with shore crabs ( Carcinus maenas ) as a model system. We found that peptide signalling cues are susceptible to protonation in future pH conditions, which will alter their overall charge. We also show that structure and electrostatic properties important for receptor binding differ significantly between the peptide forms present today and the protonated signalling peptides likely to be dominating in future oceans. The bioassays suggest an impaired functionality of the signalling peptides at low pH . Physiological changes due to high CO 2 conditions were found to play a less significant role in influencing the investigated behaviour. From our results, we conclude that the change of charge, structure and consequently function of signalling molecules presents one possible mechanism to explain altered behaviour under future oceanic pH conditions.

How the truffle got its mate: insights from genetic structure in spontaneous and planted Mediterranean populations of Tuber melanosporum - E. Taschen; F. Rousset; M. Sauve; L. Benoit; M.‐P. Dubois; F. Richard; M.‐A. Selosse (Molecular Ecology, 2016)
The life cycles and dispersal of edible fungi are still poorly known, thus limiting our understanding of their evolution and domestication. The prized Tuber melanosporum produces fruitbodies (fleshy organs where meiospores mature) gathered in natural, spontaneously inoculated forests or harvested in plantations of nursery‐inoculated trees. Yet, how fruitbodies are formed remains unclear, thus limiting yields, and how current domestication attempts affect population genetic structure is overlooked. Fruitbodies result from mating between two haploid individuals: the maternal parent forms the flesh and the meiospores, while the paternal parent only contributes to the meiospores. We analyzed the genetic diversity of T. melanosporum comparatively in spontaneous forests vs. plantations, using SSR polymorphism of 950 samples from South‐East France. All populations displayed strong genetic isolation by distance at the metric scale, possibly due to animal dispersal, meiospore persistence in soil, and/or exclusion of unrelated individuals by vegetative incompatibility. High inbreeding was consistently found, suggesting that parents often develop from meiospores produced by the same fruitbody. Unlike maternal genotypes, paternal mycelia contributed to few fruitbodies each, did not persist over years, and were undetectable on tree mycorrhizae. Thus, we postulate that germlings from the soil spore bank act as paternal partners. Paternal genetic diversity and outbreeding were higher in plantations than in spontaneous truffle‐grounds, perhaps because truffle growers disperse fruitbodies to maintain inoculation in plantations. However, planted and spontaneous populations were not genetically isolated, so that T. melanosporum illustrates an early step of domestication where genetic structure remains little affected.

Glacial Isostatic Adjustment (GIA) in Greenland: a Review - Leanne M. Wake; Benoit S. Lecavalier; Michael Bevis (Current Climate Change Reports, 2016)

Toluene diisocyanate and methylene diphenyl diisocyanate: asthmatic response and cross-reactivity in a mouse model - Lore Pollaris; Fien Devos; Vanessa De Vooght; Sven Seys; Benoit Nemery; Peter H. M. Hoet; Jeroen A. J. Vanoirbeek (Archives of Toxicology, 2016)

Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Stephen T. Spagnol; Wei-Chun Lin; Elizabeth A. Booth; Benoit Ladoux; Hillard M. Lazarus; Kris Noel Dahl (Annals of Biomedical Engineering, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Perinatal induction of Cre recombination with tamoxifen - Benoit Lizen; Melissa Claus; Lucie Jeannotte; Filippo M. Rijli; Françoise Gofflot (Transgenic Research, 2015)

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Using multi‐timescale methods and satellite‐derived land surface temperature for the interpolation of daily maximum air temperature in Oregon - Benoit Parmentier; Brian J. McGill; Adam M. Wilson; James Regetz; Walter Jetz; Robert Guralnick; Mao‐Ning Tuanmu; Mark Schildhauer (International Journal of Climatology, 2015)
There is a growing demand for fine‐grained (e.g. 1 km) daily historical meteorological data. Traditional approaches interpolate between observations collected at existing meteorological stations; however, the demand for ever increasing fine resolutions has begun to outstrip the available ground‐station data, especially for daily timescales. One promising technique known as the climate‐aided interpolation ( CAI ) has the advantage of incorporating climatological data to improve fine‐grained spatial detail while still producing a daily product. By estimating spatial structure at a coarser timescale than the target timescale, more ground‐station data can be used, leading to improved accuracy in these multi‐timescale procedures. Another approach to improve fine‐grained spatial structure is the incorporation of additional environmental covariates that are measured at fine grains. Elevation has long been used in this role, but other covariates, especially remotely sensed measures of land cover and land surface temperatures ( LST ), are also promising. In this paper, we provide a comprehensive evaluation of three interpolation methods and rigorous evaluation of multi‐timescale procedures that do and do not include additional environmental covariates including LST . We perform this evaluation on daily maximum air temperature predictions using a region with widely varying climates, the state of Oregon, USA . We find that multi‐timescale procedures provide a roughly 10% improvement in prediction accuracy over single‐timescale procedures. For multi‐timescale approaches, we find that universal kriging has the lowest root mean square error ( RMSE ) but has a lower predictive accuracy when the number of station decreases in the study area. Thus, generalized additive models ( GAM ) and geographically weighted regression ( GWR ) may be superior interpolation methods in areas with sparse station data. Most covariates other than elevation do not improve accuracy, but LST may be useful during summer when elevation displays low correlation with T max . Analyses also show that elevation and LST provide increased spatial heterogeneity.

Diguanylate cyclase D gc P is involved in plant and human P seudomonas spp. infections - Isabel M. Aragon; Daniel Pérez‐Mendoza; Joana A. Moscoso; Emmanuel Faure; Benoit Guery; María‐Trinidad Gallegos; Alain Filloux; Cayo Ramos (Environmental Microbiology, 2015)
Summary The second messenger cyclic di‐ GMP (c‐di‐ GMP ) controls the transition between different lifestyles in bacterial pathogens. Here, we report the identification of D gc P (diguanylate cyclase conserved in P seudomonads), whose activity in the olive tree pathogen P seudomonas savastanoi pv. savastanoi is dependent on the integrity of its GGDEF domain. Furthermore, deletion of the dgc P gene revealed that D gc P negatively regulates motility and positively controls biofilm formation in both the olive tree pathogen P . savastanoi pv. savastanoi and the human opportunistic pathogen P seudomonas aeruginosa . Overexpression of the dgc P gene in P . aeruginosa PAK led to increased exopolysaccharide production and upregulation of the type VI secretion system; in turn, it repressed the type III secretion system, which is a hallmark of chronic infections and persistence for P . aeruginosa . Deletion of the dgc P gene in P . savastanoi pv. savastanoi NCPPB 3335 and P . aeruginosa PAK reduced their virulence in olive plants and in a mouse acute lung injury model respectively. Our results show that diguanylate cyclase D gc P is a conserved P seudomonas protein with a role in virulence, and confirm the existence of common c‐di‐ GMP signalling pathways that are capable of regulating plant and human P seudomonas spp. infections.

Benchmarks for multicomponent reactive transport across a cement/clay interface - Nicolas C. M. Marty; Olivier Bildstein; Philippe Blanc; Francis Claret; Benoit Cochepin; Eric C. Gaucher; Diederik Jacques; Jean-Eric Lartigue; Sanheng Liu; K. Ulrich Mayer; Johannes C. L. Meeussen; Isabelle Munier; et al. (Computational Geosciences, 2015)

Using next-generation sequencing methods to isolate and characterize 24 simple sequence repeat loci in mandrills (Mandrillus sphinx) - Laure Benoit; Sylvère Mboumba; E. Willaume; P. M. Kappeler; Marie J. E. Charpentier (Conservation Genetics Resources, 2014)

Emerging roles of aquaporins in relation to the physiology of blood-feeding arthropods - Joshua B. Benoit; Immo A. Hansen; Elise M. Szuter; Lisa L. Drake; Denielle L. Burnett; Geoffrey M. Attardo (Journal of Comparative Physiology B, 2014)

Simulation of Cement/Clay Interactions: Feedback on the Increasing Complexity of Modelling Strategies - Nicolas C. M. Marty; Isabelle Munier; Eric C. Gaucher; Christophe Tournassat; Stéphane Gaboreau; Chan Quang Vong; Eric Giffaut; Benoit Cochepin; Francis Claret (Transport in Porous Media, 2014)

OsJAR1 is required for JA-regulated floret opening and anther dehiscence in rice - Yuguo Xiao; Yi Chen; Tatsiana Charnikhova; Patrick P. J. Mulder; Jeroen Heijmans; Angela Hoogenboom; Adamantia Agalou; Corinne Michel; Jean-Benoit Morel; Ludovico Dreni; Martin M. Kater; Harro Bouwmeester; et al. (Plant Molecular Biology, 2014)

Targeting VEGFR1 on endothelial progenitors modulates their differentiation potential - Clément d’Audigier; Benoit Gautier; Alexis Yon; Jean-Meidi Alili; Coralie L. Guérin; Solène M. Evrard; Anne Godier; Skerdi Haviari; Marie Reille-Serroussi; Florent Huguenot; Blandine Dizier; Nicolas Inguimbert; et al. (Angiogenesis, 2014)

Transformation of hydroxylated derivatives of 2,5-dichlorobiphenyl and 2,4,6-trichlorobiphenyl by Burkholderia xenovorans LB400 - Rouzbeh Tehrani; Monica M. Lyv; Benoit Van Aken (Environmental Science and Pollution Research, 2014)

Structure and fate of a Pseudomonas aeruginosa population originating from a combined sewer and colonizing a wastewater treatment lagoon - Raphaël Lavenir; Stéphanie M.-C Petit; Nolwenn Alliot; Sébastien Ribun; Laurence Loiseau; Laurence Marjolet; Jérôme Briolay; Sylvie Nazaret; Benoit Cournoyer (Environmental Science and Pollution Research, 2014)

Pesticide risk assessment and management in a globally changing world—report from a European interdisciplinary workshop - Marc Babut; Gertie H. Arts; Anna Barra Caracciolo; Nadia Carluer; Nicolas Domange; Nikolai Friberg; Véronique Gouy; Merete Grung; Laurent Lagadic; Fabrice Martin-Laurent; Nicolas Mazzella; Stéphane Pesce; et al. (Environmental Science and Pollution Research, 2013)

Seasonal Mercury Dynamics in a New England Vernal Pool - Janina M. Benoit; Deborah A. Cato; Katherine C. Denison; Amy E. Moreira (Wetlands, 2013)

Archaeal diversity from hydrothermal systems of Deception Island, Antarctica - Maximiliano J. Amenábar; Patricio A. Flores; Benoit Pugin; Freddy A. Boehmwald; Jenny M. Blamey (Polar Biology, 2013)

Evolutionary history of almond tree domestication in the M editerranean basin - M. Delplancke; N. Alvarez; L. Benoit; A. Espíndola; H. I Joly; S. Neuenschwander; N. Arrigo (Molecular Ecology, 2013)
Genetic diversity of contemporary domesticated species is shaped by both natural and human‐driven processes. However, until now, little is known about how domestication has imprinted the variation of fruit tree species. In this study, we reconstruct the recent evolutionary history of the domesticated almond tree, Prunus dulcis , around the Mediterranean basin, using a combination of nuclear and chloroplast microsatellites [i.e. simple sequence repeat ( SSR s)] to investigate patterns of genetic diversity. Whereas conservative chloroplast SSR s show a widespread haplotype and rare locally distributed variants, nuclear SSR s show a pattern of isolation by distance with clines of diversity from the East to the West of the Mediterranean basin, while Bayesian genetic clustering reveals a substantial longitudinal genetic structure. Both kinds of markers thus support a single domestication event, in the eastern side of the Mediterranean basin. In addition, model‐based estimation of the timing of genetic divergence among those clusters is estimated sometime during the Holocene, a result that is compatible with human‐mediated dispersal of almond tree out of its centre of origin. Still, the detection of region‐specific alleles suggests that gene flow from relictual wild preglacial populations (in North Africa) or from wild counterparts (in the Near East) could account for a fraction of the diversity observed.

Extreme Conservation of the psaA/psaB Intercistronic Spacer Reveals a Translational Motif Coincident with the Evolution of Land Plants - Elena L. Peredo; Donald H. Les; Ursula M. King; Lori K. Benoit (Journal of Molecular Evolution, 2012)

Biodegradation of mono-hydroxylated PCBs by Burkholderia xenovorans - Rouzbeh Tehrani; Monica M. Lyv; Rashid Kaveh; Jerald L. Schnoor; Benoit Aken (Biotechnology Letters, 2012)

Mineralogy, geochemistry and petrogenesis of the recent magmatic formations from Mbengwi, a continental sector of the Cameroon Volcanic Line (CVL), Central Africa - Benoît Joseph Mbassa; Emmanuel Njonfang; Mathieu Benoit; Pierre Kamgang; Michel Grégoire; Stephanie Duchene; Pierre Brunet; Bekoa Ateba; Félix M. Tchoua (Mineralogy and Petrology, 2012)

Effects of prenatal immune activation and peri-adolescent stress on amphetamine-induced conditioned place preference in the rat - Neil M. Richtand; Rebecca Ahlbrand; Paul S. Horn; Brad Chambers; Jon Davis; Stephen Benoit (Psychopharmacology, 2012)

Observations of Thin Layers in Coastal Hawaiian Waters - Margaret A. McManus; Jeff C. Sevadjian; Kelly J. Benoit-Bird; Olivia M. Cheriton; Amanda H. V. Timmerman; Chad M. Waluk (Estuaries and Coasts, 2012)

Genetic structure in a dynamic baboon hybrid zone corroborates behavioural observations in a hybrid population - M. J. E. CHARPENTIER; M. C. FONTAINE; E. CHEREL; J. P. RENOULT; T. JENKINS; L. BENOIT; N. BARTHÈS; S. C. ALBERTS; J. TUNG (Molecular Ecology, 2012)
Behaviour and genetic structure are intimately related: mating patterns and patterns of movement between groups or populations influence the movement of genetic variation across the landscape and from one generation to the next. In hybrid zones, the behaviour of the hybridizing taxa can also impact the incidence and outcome of hybridization events. Hybridization between yellow baboons and anubis baboons has been well documented in the Amboseli basin of Kenya, where more anubis‐like individuals tend to experience maturational and reproductive advantages. However, it is unknown whether these advantages are reflected in the genetic structure of populations surrounding this area. Here, we used microsatellite genotype data to evaluate the structure and composition of baboon populations in southern Kenya. Our results indicate that, unlike for mitochondrial DNA, microsatellite‐based measures of genetic structure concord with phenotypically based taxonomic distinctions and that the currently active hybrid zone is relatively narrow. Isolation with migration analysis revealed asymmetric gene flow in this region from anubis populations into yellow populations, in support of the anubis‐biased phenotypic advantages observed in Amboseli. Populations that are primarily yellow but that receive anubis gene flow exhibit higher levels of genetic diversity than yellow populations far from the introgression front. Our results support previous work that indicates a long history of hybridization and introgression among East African baboons. Specifically, it suggests that anubis baboons are in the process of gradual range expansion into the range of yellow baboons, a pattern potentially explained by behavioural and life history advantages that correlate with anubis ancestry.

Immunohistochemical assessment of Pax8 expression during pancreatic islet development and in human neuroendocrine tumors - Petra I. Lorenzo; Carmen M. Jimenez Moreno; Irene Delgado; Nadia Cobo-Vuilleumier; Raphael Meier; Lourdes Gomez-Izquierdo; Thierry Berney; Rocio Garcia-Carbonero; Anabel Rojas; Benoit R. Gauthier (Histochemistry and Cell Biology, 2011)

Defining the Turkey MHC: identification of expressed class I- and class IIB-like genes independent of the MHC-B - Kent M. Reed; Miranda M. Bauer; Melissa S. Monson; Benjamin Benoit; Lee D. Chaves; Thomas H. O’Hare; Mary E. Delany (Immunogenetics, 2011)

Assessment of the Design of an Experimental Cover with Capillary Barrier Effect Using 4 Years of Field Data - Amir M. Abdolahzadeh; Benoit Lacroix Vachon; Alexandre R. Cabral (Geotechnical and Geological Engineering, 2011)

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

An Environmental Model Predicting Bacterial Ring Rot Symptom Expression - Bernard D. Hill; Melanie Kalischuk; Doug R. Waterer; Benoit Bizimungu; Ron Howard; Lawrence M. Kawchuk (American Journal of Potato Research, 2011)

Estimating aquifer thickness using multiple pumping tests - Jean-Christophe Maréchal; Jean-Michel Vouillamoz; M. S. Mohan Kumar; Benoit Dewandel (Hydrogeology Journal, 2010)

Inhibition of fatty acid amide hydrolase reduces reinstatement of nicotine seeking but not break point for nicotine self-administration—comparison with CB1 receptor blockade - Benoit Forget; Kathleen M. Coen; Bernard Le Foll (Psychopharmacology, 2009)

Real-time monitoring of angiotensin II-induced contractile response and cytoskeleton remodeling in individual cells by atomic force microscopy - Charles M. Cuerrier; Martin Benoit; Gaétan Guillemette; Fernand Jr. Gobeil; Michel Grandbois (Pflügers Archiv - European Journal of Physiology, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Influence of agricultural practices on micrometerological spatial variations at local and regional scales - D. Courault; F. Jacob; V. Benoit; M. Weiss; O. Marloie; J. F. Hanocq; E. Fillol; A. Olioso; G. Dedieu; P. Gouaux; M. Gay; A. French (International Journal of Remote Sensing, 2009)

Antarctic Collembolans Use Chemical Signals to Promote Aggregation and Egg Laying - J. B. Benoit; M. A. Elnitsky; G. G. Schulte; R. E. Lee; D. L. Denlinger (Journal of Insect Behavior, 2009)

Adaptations for the maintenance of water balance by three species of Antarctic mites - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Polar Biology, 2008)

Parasite Prevalence, Abundance, and Diversity in a Semi-free-ranging Colony of Mandrillus sphinx - Joanna M. Setchell; Issa-Ben Bedjabaga; Benoit Goossens; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (International Journal of Primatology, 2007)

Habitat requirements of the seabird tick, Ixodes uriae (Acari: Ixodidae), from the Antarctic Peninsula in relation to water balance characteristics of eggs, nonfed and engorged stages - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Journal of Comparative Physiology B, 2007)

Towards Positional Cloning in Brassica napus: Generation and Analysis of Doubled Haploid B. rapa Possessing the B. napus pol CMS and Rfp Nuclear Restorer Gene - Nataša Formanová; Xiu-Qing Li; Alison M. R. Ferrie; Mary DePauw; Wilf A. Keller; Benoit Landry; Gregory G. Brown (Plant Molecular Biology, 2006)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.

AtGLR3.4, a glutamate receptor channel-like gene is sensitive to touch and cold - Oliver Meyerhoff; Katharina Müller; M. Rob G. Roelfsema; Andreas Latz; Benoit Lacombe; Rainer Hedrich; Petra Dietrich; Dirk Becker (Planta, 2005)

Dichlorvos degradation studied by 31P-NMR - F. Benoit-Marquié; C. de Montety; V. Gilard; R. Martino; M. T. Maurette; M. Malet-Martino (Environmental Chemistry Letters, 2004)

Water relations in eggs of the lone star tick, Amblyomma americanum, with experimental work on the capacity for water vapor absorption - Jay A. Yoder; Joshua B. Benoit; Amanda M. Opaluch (Experimental and Applied Acarology, 2004)

Activation of the hexose monophosphate shunt in rat type II pneumocytes as an early marker of oxidative stress caused by cobalt particles - Peter M. Hoet; Goedele Roesems; Maurits G. Demedts; Benoit Nemery (Archives of Toxicology, 2002)

Response of Avian Communities to Historic Habitat Change in the Northern Chihuahuan Desert - A. M. Pidgeon; N. E. Mathews; R. Benoit; E. V. Nordheim (Conservation Biology, 2001)
Throughout much of the northern Chihuahuan Desert, the grasslands that were widespread at the time of European settlement have been replaced by desert shrublands. Little is known about the effects of this change on avian communities. We analyzed historic U.S. Government Land Office records to assess large‐scale changes in vegetation cover from the 1880s to the present day. We studied vegetation and avian communities in one grassland habitat type and four desert shrubland habitat types to examine (1) how breeding‐bird communities may have changed in response to habitat conversion from grassland to desert shrubland and (2) whether breeding‐bird communities differ among the four desert shrubland habitat types that compose Chihuahuan Desert scrub in this region. To estimate the characteristics of 1880s black grama ( Bouteloua eriopoda ) grassland, we focused on plots located within extensive patches of present‐day black grama and compared the avian communities found there with those in desert shrubland. Species richness was higher in desert shrubland than grassland. Among the desert shrubland habitat types, species richness was consistently highest in mesquite. Avian abundance patterns differed among the four desert shrubland habitat types. At least 30% of the avian community in each habitat pair was distinct. Conversion of grassland to shrubland in south‐central New Mexico has likely been accompanied by a major turnover in the avian community. Remaining tracts of black grama provide habitat for species that may be uniquely adapted to the northern Chihuahuan Desert and should be protected.

Energy, transport and waste models - Jan Braam; Toini M. Tanner; Cecilia Askham; Nicoline Hendriks; Benoit Maurice; Helena Mälkki; Mie Vold; Helena Wessman; Angeline S. H. de Beaufort (The International Journal of Life Cycle Assessment, 2001)

Experimental study of the ground motion on a large scale topographic hill at Kitherion (Greece) - Benoit LeBrun; D. Hatzfeld; P.Y. Bard; M. Bouchon (Journal of Seismology, 1999)

Physical Aging of Progesterone-Loaded Poly(D,L,-lactide-co-glycolide) Microspheres - V. Rosilio; M. Deyme; J. P. Benoit; G. Madelmont (Pharmaceutical Research, 1998)

Lateral forces in AFM imaging and immobilization of cells and organelles - M. Benoit; T. Holstein; H. E. Gaub (European Biophysics Journal, 1997)

Tissue distribution metabolism and excretion of 2,2?,4,4?, 5-pentachlorodiphenyl ether in the rat - E. Komsta; I. Chu; D. C. Villeneuve; F. M. Benoit; D. Murdoch (Archives of Toxicology, 1988)

Choix de l'hôte et comportement trophique des larves deTrichogramma evanescens [Hym.: Trichogrammatidae] en fonction du développement embryonnaire deEphestia kuehniella etOstrinia nubilalis [Lep.: Pyralidae] - M. Benoit; J. Voegelé (BioControl, 1979)